ANALYSIS OF THE NEED FOR RENEWAL OF MATHEMATICS TEACHING MATERIALS IN VOCATIONAL HIGH SCHOOL - Agus Nurdiyanto; Nurhanurawati Nurhanurawati (Prima: Jurnal Pendidikan Matematika, 2022)
Teaching materials are an important in the implementation of education. Teaching materials have to the needs and attract students' interest in learning. Teaching materials must also be able to assist teachers in delivering subject matter. From the results of observations of teaching materials in vocational students, researchers found data that the delivery of materials in teaching materials was quite monotonous. The presentation of this monotonous material does not attract students' interest in using teaching materials. This research is a descriptive qualitative research. The place of this research is a vocational high school (SMK) State 3 Metro, Lampung Province. The research subjects used were 8 students and 3 mathematics teachers at SMKN 3 Metro. The research instrument used was a questionnaire sheet and an interview guide. The data analysis technique uses the Miles and Huberman stages, namely: data reduction, data presentation, and drawing conclusions. Based on result and discussion show that materials teaching mathematics for vocational students are needed novelty of: 1) systematic preparation, 2) materials adapted to the characteristics of vocational students, 3) presentation of teaching materials adapted to technological developments, 4) use of technology to attract students' interest, 5) the form of teaching materials that are more practical and easy to use. AbstrakBahan ajar merupakan bagian penting dalam pelaksanaan Pendidikan. Bahan ajar yang baik harus bisa memenuhi kebutuhan dan menarik minat peserta didik dalam belajar. Bahan ajar juga harus dapat membantu guru dalam menyampaikan materi pelajaran. Dari hasil observasi bahan ajar pada siswa SMK, peneliti menemukan data bahwa penyampaian materi pada bahan ajar cukup monoton. Penyajian materi yang monoton ini kurang menarik minat siswa dalam menggunakan bahan ajar. Penelitian ini merupakan penelitian kualitatif deskriptif. Tempat penelitian ini adalah sekolah menengah kejuruan (SMK) Negeri 3 Metro Provinsi Lampung. Subyek penelitian yang digunakan adalah 8 orang siswa dan 3 orang guru matematika SMKN 3 Metro. Instrumen penelitian yang digunakan adalah lembar angket dan pedoman wawancara.  Teknik analisis data menggunakan tahapan Miles dan Huberman yaitu : reduksi data, penyajian data, dan penarikan kesimpulan. Berdasarkan hasil analisis data dan pembahasan dapat disimpulkan bahwa diperlukan pembaruan bahan ajar matematika siswa SMK berupa : 1) sistematika penyusunan berbeda, 2) materi yang disesuaikan dengan karakteristik siswa SMK, 3) penyajian bahan ajar yang disesuaikan dengan perkembangan teknologi, 4) penggunaan teknologi untuk menarik minat siswa, 5) bentuk bahan ajar yang lebih praktis dan mudah digunakan.